Defining a universal measurement unit and scale for gross motor development - Seamon, Bryant A.; Sears, Cynthia L.; Anderson, Emily; Velozo, Craig A. (Frontiers in Rehabilitation Sciences, 2024)
The ability of children to accomplish progressively more difficult gross motor tasks follows a predictable sequence that has been well documented as part of development. Current existing instruments were developed independently using classical test theory methods which led to the lack of a universal measurement scale and unit. The purpose of this study was to test a specification equation, anchored to commonly accepted and reproducible tasks in gross motor development, to generate a universal measurement scale and unit of measurement, called the Gross Motor (GM) unit. We rated component measures for each of the gross motor development tasks on the Gross Motor Function Measure-66 (GMFM). The GMFM is a gross motor development measure created with Rasch measurement theory to quantify observed difficulty levels measured on an interval scale. Component measures for body position, movement, and support were based on hypothesized contributions to gross motor development based on theory. Forward stepwise linear regression was used to test a specification equation. The specification equation was anchored to reference points to fix a unit size. Our specification equation explained 87% of the variance in observed gross motor task difficulty. Predicted difficulty for gross motor tasks was strongly associated with observed task difficulty (r=0.94, p<0.0001). Our specification equation was anchored to 1) lying supine (0 GM units) and 2) walking unsupported (100 GM units) setting the size of the GM unit to 1/100 of the distance between lying supine and unsupported walking. Our specification equation allows for experimental testing of gross motor development theories. This approach provides a framework for refining our understanding and measurement of gross motor development and creates a universal scale and unit. We expect that this will facilitate placing many, if not all, current gross motor development instruments on the same measurement scale.